2009
DOI: 10.1007/s11666-009-9420-4
|View full text |Cite
|
Sign up to set email alerts
|

Mullite and Mullite/ZrO2-7wt.%Y2O3 Powders for Thermal Spraying of Environmental Barrier Coatings

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Mullite and mullite/ZrO₂-7wt%Y₂O₃ powders for thermal spraying of environmental barrier coatings Garcia, E.; Mesquita-Guimaraes, J.; Miranzo, P.; Osendi, M. I.; Wang, Y.; Lima, R. S.; Moreau, C.http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=fr L'accès à ce site Web et l'utilisation de son contenu sont assujettis aux conditions présentées dans le site LISEZ CES CONDITIONS ATTENTIVEMENT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Similarly, the YAS-GNP powders were FS into a metal container filled with liquid N 2 for attaining flame spheroidized beads. 39 These beads helped to understand changes occurring in the YAS-GNP granules throughout the spraying process.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Similarly, the YAS-GNP powders were FS into a metal container filled with liquid N 2 for attaining flame spheroidized beads. 39 These beads helped to understand changes occurring in the YAS-GNP granules throughout the spraying process.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Suspensions with 30 wt.% of solid contents of mullite and mullite/Y-ZrO 2 mixtures were prepared and spray dried (SD), in the same way as described in a previous work (Ref 11), to get the feedstock powders with a particle size of À60/+5 lm. Alternatively, a batch of mullite was prepared following a CSIC proprietary freeze-granulation (FG) method from the same starting powders; the particle size of the FG feedstock was À150/+32 lm.…”
Section: Methodsmentioning
confidence: 99%
“…The literature survey has revealed that there are number of environment barrier coating techniques such as HVOF, APS and EV-PVD Techniques (5,6). But an advancement of wet powder spray, Slurry Spray Technique (SST) has been emerged as a low cost, simple and effective technique (5).The Slurry Spray Technique (SST) utilizes traditional wet powder spraying methods to deposit coating materials onto a target substrate to produce a functional coating.…”
Section: Slurry Spray Techniquementioning
confidence: 99%